Efektivitas Penanganan Keluhan Pasien Pelayanan Kesehatan di Rumah Sakit Bahteramas Sulawesi Tenggara - Suhadi Suhadi; Alimin Maidin; Sukri Palutturi; Burhanuddin Bahar; Nurmaladewi Nurmaladewi; Esti Astuty (Faculty of Public Health, Hasanuddin University, Makassar, 2019)
to society, but the providing service must be quality and satisfying for patients. One measure of the successof the service is a complete complaint handling system. This study aims to analyze the effectiveness of the handlingof health service complaints in the Bahteramas Hospital of Southeast-Sulawesi Province. This is a qualitativeresearch, with case-study approach. Informants are patients and staff of the hospital. Collection data conducted byin-depth interviews, observation and document review. The results indicate that the handling of complaints of healthservices in hospitals has not been entirely effective. In its implementation, there were still many problems includingcomplaint-handling obstacles, unclear complaint-handling information, partly refusal complaint-handling, aslow complaint-handling, lack of officers’ sympathy, lack of complaint-handling solutions, no explanation fromthe officer, no complaint-handling unit. The implementation of complaints handling in Bahteramas Hospital hasnot been effective, there were still some problems faced, namely the aspects of service quality, organizationalbehavior and service resources. There are some items needed to enhance by the hodpital namely improvementof policies, service management, education and training for officers, and fulfillment of service resource needs.